RETAIN: A Board Game That Improves Neonatal Resuscitation Knowledge Retention - Cutumisu, Maria; Patel, Siddhi D.; Brown, Matthew R. G.; Fray, Caroline; von Hauff, Patrick; Jeffery, Thomas; Schmölzer, Georg M. (Frontiers in Pediatrics, 2019)
Background More than two thirds of neonatal deaths are attributed to human errors during resuscitation. Therefore, the current resuscitation guidelines recommend frequent simulation based medical education (SBME). However, the current SBME approach is expensive, time-intensive, and requires a specialized lab and trained instructors. Hence, it is not offered routinely at all hospitals. We designed the board game “RETAIN” to train healthcare providers (HCPs) in neonatal resuscitation in a cost-friendly and accessible way. Objectives To examine if a board game-based training simulator improves knowledge retention in HCPs. Methods “RETAIN” consists of a board using an image of a baby, visual objects, adjustable timer, monitors, and action cards. Neonatal HCPs at the Royal Alexandra Hospital were invited to participate. Participants completed a written pre-test (resuscitation of a 24-week infant), then played the board game (starting with a tutorial followed by free playing of three evidence-based neonatal resuscitation scenarios). Afterwards, a post-test with the same resuscitation scenario and an opinion survey was completed. The answers from the pre- and post-test were compared to assess HCPs’ knowledge retention. Results Thirty HCPs (four doctors, 12 nurses, and 14 respiratory therapist) participated in the study. Overall, we observed a 10% increase in knowledge retention between the pre- and post-test (49% to 59%, respectively). Temperature management showed the most knowledge gain between the pre- and post-test (14% to 46%, respectively). Placement of a hat (10% to 43%), plastic wrap (27% to 67%), and temperature probe (7% to 30%) improved between the pre- and post-test. Conclusion Knowledge retention increased by 12% between pre- and post-test (49% to 61%, respectively). The improvement in performance and knowledge supports the use of board game simulations for clinical training.